The proposed model of pulse code modulation encoder for voice frequencies - Ahmed, Iftekhar Uddin; Masum, Abdul Kadar Muhammad; Motakabber, S.M.A (International Journal of Scientific World, 2015)
In this paper, we have developed a hardware-based model of pulse code modulation (PCM) system for voice frequencies. Firstly, we have constructed sample and hold circuit using triggered semiconductor switch (e.g., MOSFET), which is capable of sampling voice signals at 8 kHz according to Nyquist theory. Then an Analogue to Digital Converter (ADC) Integrated Circuit (IC) is introduced to quantize and to digitize of the output of the sample and hold as pulse amplitude modulation (PAM). The converted outputs are 8-bit digital parallel value per sample at a frequency of 8 kHz. Finally, a parallel to serial converter logic is constructed which remains the voice frequency at the accurate time without any delay. The principle feature of this PCM system is that during a final interval of time, it makes a waveform into 8 bit serial code word. An 8-bit shift register with decade counter and flip-flop based logic are providing to this wave-from one after another without any interruptions of the sequences.